KEPENTINGAN INDONESIA MENGEKSPOR SALAK PONDOH KE SELANDIA BARU 2017-2018 - Darwinda "; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
New Zealand is one of the trading partners in an important cooperation for Indonesia. As countries that are open in their economies, Indonesia and New Zealand hope that trade relations can be established and produce mutually beneficial relations. The cooperation to export salak pondoh has long been initiated. Starting from New Zealand's commitment in 2006 when providing assistance to victims of the volcano and there is a trade opportunity provided that the product meets the requirements set by the destination country of New Zealand. In discussing the problems in this research, the author uses a qualitative method that is supported by the perspective of Liberalism and the state as the level of analysis and with the theory of cooperation to analyze the interests obtained. This research shows that the cooperation in the export of Indonesian salak pondoh to New Zealand has a good impact on the quality of Indonesian fruit for export. The interests between the two countries are mutually beneficial where Indonesia and New Zealand need each other's Export and Import products. Where the economic and political interests of the two countries are interconnected with one another. Keywords: Export, Import, Salak Pondoh, economy, politics and Indonesian farmers